Al-’alaqah Bayna al-Mauqif al-Lughawiyyah wa al-Tahshil al-Ilmiy li al-Ta’lim al-Lughah al-Arabiyyah - Akhsan, Akhsan; Ahmadi M; Khoirul Anwar (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
This Research was conducted to determine the relationship between language attitudes and Arabic learning achievment of students at Madrasah Tsanawiyah Negeri 1 Situbondo, academic year 2021/2022. This type of research is a quantitative research with a correlational approach. Data obtained by quetionnaire method and documentation. The research population was class VIII students of Madrasah Tsanawiyah Negeri 1 Situbondo wich consisted of 34 students. Samples were taken randomly as many as 31 students according to the slovin formula. Data analysis techniques include assumption tests (normality test and linearity test) and hypothesis testing (correlation test, correlation coefficient significance test and ditermination test). the result showed that : 1) There was a positive and significant relaationship between language attitudes and Arabic learning achievement with a correlation coefficient of 0.673, 2) The result of the significance test of the correlation coefficient showed t (table) > t (cont) (4.819 > 2.048), 3) Language attitudes have a proportion in determining Arabic learning achievement 0f 45.29 %.